The fiscal effects of economic immigration on subnational government finance in Poland - Marzanna Poniatowicz; Agnieszka Piekutowska (e-Finanse: Financial Internet Quarterly, 2019)
The aim of the paper is to analyse the effects of economic immigration on subnational government finance (SNG) in Poland. The goal to achieve is to answer the following research question: what are the fiscal effects of immigration on SNG budget revenues and expenditures. To answer this question, logarithmic models were developed. The analysis refers to the years 2007-2016. In this respect, data from Statistics Poland - referring to budget revenues and expenditures of communes, cities of district status, districts and voivodeships - were used. As far as immigration statistics are concerned, data from the Ministry of Family, Labour and Social Policy were used. The results indicate an increase in both revenues and expenditures of SNG as a result of immigration. Such results can be explained inter alia by the nature of migration - research were focused on economic immigration. Results confirm that the level of employment of foreigners is one of the determinants shaping the fiscal effect of immigration. Moreover, the impact of economic immigration on SNG budget revenues and expenditures depends on the structure of this budget. This explains the differentiated results of the analysis of the impact of immigration on SNG in different countries. The positive correlation between immigration and SNG revenues in Poland can be associated with a high share of subnational governments in personal income tax revenues as this tax is one of the main categories of SNG revenues.
Keywords: F22; H72; 330; economic immigration; subnational government finance; budgets' revenues and expenditures